Empirical Study of Multi-Objective Risk Portfolio Optimization Based on NSGA-II - Qian Gao; Aleš Kresta (Finanse i Prawo Finansowe)
The purpose of the article. The application of multi-objective optimization in portfolio management has gained significant attention in asset management. This study aims to uncover the potential advantages of dynamic portfolio optimization using a multi-objective genetic algorithm to address the challenges of ever-changing market conditions.